2020
DOI: 10.1007/s12325-020-01300-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Utilisation and Bleed Rates in Patients with Haemophilia B Who Switched to Recombinant Factor IX Fusion Protein (rIX-FP): A Retrospective International Analysis

Abstract: Introduction: Despite the well-documented benefits of prophylaxis, treatment burden is still a barrier to adherence in patients with haemophilia. An extended half-life fusion protein linking recombinant FIX (rFIX) with human albumin (rIX-FP) has been developed for the treatment of patients with haemophilia B and is indicated for dosing up to every 14 days. This analysis evaluated real-world outcomes in patients switching to rIX-FP from the previous FIX product in Italy, Belgium and the UK. Methods: Anonymised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 25 publications
2
28
1
2
Order By: Relevance
“…In addition to data from PROLONG-9FP studies, real-world clinical data has been collated and analyzed to determine the effectiveness, safety, and clinical response of rIX-FP in routine clinical practice. Two post-marketing studies have used retrospective patient chart data to compare bleeding rates, FIX product consumption, and dosing regimens in adult/adolescent and pediatric patients with hemophilia B who switched from prior FIX prophylaxis to rIX-FP prophylaxis [30,31].…”
Section: Clinical Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to data from PROLONG-9FP studies, real-world clinical data has been collated and analyzed to determine the effectiveness, safety, and clinical response of rIX-FP in routine clinical practice. Two post-marketing studies have used retrospective patient chart data to compare bleeding rates, FIX product consumption, and dosing regimens in adult/adolescent and pediatric patients with hemophilia B who switched from prior FIX prophylaxis to rIX-FP prophylaxis [30,31].…”
Section: Clinical Experiencementioning
confidence: 99%
“…The second post-marketing study identified 73 patients treated in 23 centers in Italy (n = 13), Belgium (n = 3) and the UK (n = 7) who switched to rIX-FP prophylaxis from prior FIX therapy [31]. Overall, 92.8% of patients had severe hemophilia B (Italy: 98%; Belgium: 70%; UK: 92%).…”
Section: Clinical Experiencementioning
confidence: 99%
“…The administration of rIX-FP increased the proportion of patients experiencing zero spontaneous bleeds from 41% to 88%. Dosing and frequency of administration were also reduced after the switch [31].…”
Section: Real-world Evidence Using Rix-fpmentioning
confidence: 98%
“…A recent real world study found that the cost per success (defined as patients experiencing no spontaneous bleeding) in patients switching from nonacog alfa to rIX-FP was reduced by 29% in Italy, 55% in Belgium, and 50% in the United Kingdom. The reduction continued to be true even when the price of nonacog alfa or when the efficacy of rIX-FP were reduced by 20% [31]. Patients with complications, such as arthropathies, severe muscle hematomas, and life-threatening hemorrhages, or those who are to undergo surgery, are also good candidates for prophylaxis with rIX-FP (Figure 1).…”
Section: Expert Opinionmentioning
confidence: 99%
“…Кроме того, по результатам проведенного анализа, было показано снижение общего количества использованного препарата для проведения профилактического лечения -в среднем на 40 % [13], а по некоторым данным -на 54-58 % [19], чем при применении О б з о р ы л и т е р а т у р ы || L i t e r a t u r e r e v i e w s ранее использовавшихся факторов свертывания. Использование препаратов с удлиненным периодом полувыведения позволит повысить эффективность проводимого лечения в условиях ограниченного количества концентратов [1,20,21] .…”
Section: о б з о р ы л и т е р а т у р ы || L I T E R a T U R E R E Vunclassified